Pulmonary valve atresia with intact ventricular septum: A case report (Research, Society and Development, 2024)
Objective: To evaluate the neurodevelopmental progress of a child clinically diagnosed with pulmonary valve atresia at the physiotherapy clinic of the State University of Paraiba (UEPB), using the Alberta Infant Motor Scale (AIMS). Method: This is a descriptive case report with a quantitative and cross-sectional approach, conducted at a Physiotherapy School Clinic. The aim was to evaluate a child clinically diagnosed with pulmonary valve atresia and complete interventricular septal defect, who was referred for physiotherapy treatment. The assessment tools used included a sociodemographic evaluation form and the AIMS. This study was approved by the UEPB Research Ethics Committee - CAAE: 74237223.1.0000.5187. Results: A 7-month-old female infant, born at full term and appropriate for gestational age, was identified. The clinical diagnosis was made soon after birth, and the infant underwent thoracic surgery to correct the malformation. The child exhibited growth retardation, as evidenced by low weight and height measurements for her age group. The AIMS results revealed significant deficits in motor development, particularly in head control, rotation, prone posture, and locomotion.  Conclusion: This case highlights the importance of physiotherapy assessment and intervention in children with pulmonary valve atresia. The use of evaluative instruments allowed for the identification of the child's motor difficulties and the development of a specific treatment plan. Future studies are warranted to investigate more effective therapeutic approaches to improve respiratory function and motor development.